2021
DOI: 10.1038/s41541-021-00414-4
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 ferritin nanoparticle vaccine induces robust innate immune activity driving polyfunctional spike-specific T cell responses

Abstract: The emergence of variants of concern, some with reduced susceptibility to COVID-19 vaccines underscores consideration for the understanding of vaccine design that optimizes induction of effective cellular and humoral immune responses. We assessed a SARS-CoV-2 spike-ferritin nanoparticle (SpFN) immunogen paired with two distinct adjuvants, Alhydrogel® or Army Liposome Formulation containing QS-21 (ALFQ) for unique vaccine evoked immune signatures. Recruitment of highly activated multifaceted antigen-presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 61 publications
(31 reference statements)
0
46
0
Order By: Relevance
“…Herein, we describe the results of a statistically balanced nonhuman primate study in which we evaluated the efficacy of SARS-CoV-2 SpFN protein nanoparticle vaccine against a robust and high-titer SARS-CoV-2 respiratory (IT) and mucosal (IN) challenge. Efficacy and/or immunogenicity of this vaccine has been demonstrated in mice, hamsters, and rhesus macaques [ 17 , 18 , 19 ], including efficacy against the Alpha and Beta variants of SARS-CoV-2 demonstrated in hamsters [ 19 ]. CM were chosen for the present study as this model reproduces several human disease characteristics and provides two ideal objective and relevant endpoint criteria for efficacy evaluations: fever and viral RNA in NP swabs [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we describe the results of a statistically balanced nonhuman primate study in which we evaluated the efficacy of SARS-CoV-2 SpFN protein nanoparticle vaccine against a robust and high-titer SARS-CoV-2 respiratory (IT) and mucosal (IN) challenge. Efficacy and/or immunogenicity of this vaccine has been demonstrated in mice, hamsters, and rhesus macaques [ 17 , 18 , 19 ], including efficacy against the Alpha and Beta variants of SARS-CoV-2 demonstrated in hamsters [ 19 ]. CM were chosen for the present study as this model reproduces several human disease characteristics and provides two ideal objective and relevant endpoint criteria for efficacy evaluations: fever and viral RNA in NP swabs [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This antigen complex was combined with an adjuvant to promote a robust immune response following vaccination. We previously reported the immunogenicity of SpFN adjuvanted with either aluminum hydroxide (AlOH 3 ) or Army Liposomal Formulation QS-21 (ALFQ) in mice, and observed increased humoral and T cell responses with ALFQ [ 17 ]. Subsequent vaccine efficacy studies of SpFN-ALFQ demonstrated protection against disease and viral replication in the respiratory tract of Syrian golden hamsters, and against viral replication in rhesus macaques [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we describe the results of a statistically-balanced nonhuman primate study in which we evaluated the efficacy of SARS-CoV-2 SpFN protein nanoparticle vaccine against a robust and high-titer SARS-CoV-2 respiratory (IT) and mucosal (IN) challenge. Efficacy and/or immunogenicity of this vaccine has been demonstrated in mice, hamsters, and rhesus macaques [17, 19, 31], including efficacy against the Alpha and Beta variants of SARS-CoV-2 demonstrated in hamsters [19]. CM were chosen for the present study as this model reproduces several human disease characteristics and provides two ideal objective and relevant endpoint criteria for efficacy evaluations: fever and viral RNA in nasopharyngeal swabs [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…This antigen complex was combined with an adjuvant to promote a robust immune response following vaccination. We previously reported the immunogenicity of SpFN adjuvanted with either aluminum hydroxide (AlOH3) or Army Liposomal Formulation QS-21 (ALFQ) in mice, and observed increased humoral and T cell responses with ALFQ [17]. Subsequent vaccine efficacy studies of SpFN-ALFQ demonstrated protection against disease and viral replication in the respiratory tract of Syrian golden hamsters, and against viral replication in rhesus macaques [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…The SARS‐CoV‐2 spike ferritin nanoparticle (SpFN) is a COVID‐19 vaccine candidate produced per the abovementioned protocol by fusing the ectodomain of the prefusion S protein of SARS‐CoV‐2 with ferritin. [ 131 ] The SARS‐CoV‐2 spike ferritin nanoparticle paired with Alhydrogel ® (ALFQ), a liposomal formulation and alum‐containing adjuvant, could provide broad neutralizing protection in nonhuman primates. [ 132 ] The SpFN+ ALFQ‐induced T‐cell response spectrum was further assessed in mice.…”
Section: Nanotechnology Enabled Covid‐19 Vaccine Developmentmentioning
confidence: 99%